Vibrio Flagellar Synthesis - Echazarreta, Mylea A.; Klose, Karl E. (Frontiers in Cellular and Infection Microbiology, 2019)
Vibrio spp. are highly motile Gram-negative bacteria, ubiquitously found in marine environments. Some Vibrios are responsible for disease and morbidity of marine invertebrates and humans, while others are studied for their symbiotic interactions. Vibrio spp. are motile due to synthesis of flagella that rotate and propel the bacteria. Many Vibrio spp. synthesize monotrichous polar flagella (e.g. V. cholerae, V. alginolyticus); however, some synthesize peritrichous or lophotrichous flagella. Flagellar-mediated motility is intimately connected to processes such as chemotaxis, biofilm formation, colonization and virulence of Vibrio spp. This review focuses on the polar flagellum and its regulation in regard to Vibrio virulence and environmental persistence.